Debtors Deferring Debt Payment Obligations and Repeated Appeals in the Perspective of Legal Certainty: Debitor Penundaan Kewajiban Pembayaran Utang dan Kasasi Berulang dalam Perspektif Kepastian Hukum - Ananda, Hauwra; Adam, Richard C. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Suspension of Debt Payment Obligations (PKPU) serves as a preventive legal mechanism in Indonesian economic law, allowing debtors to restructure obligations and avoid bankruptcy. Specific Background: However, after the Constitutional Court Decision No. 23/PUU-XIX/2021, which opened the possibility of cassation against PKPU rulings, debtors began to exploit this right, filing multiple cassations that delay dispute resolution. Knowledge Gap: Law No. 37 of 2004 concerning Bankruptcy and PKPU does not explicitly regulate the frequency or limits of cassation filings, creating a normative void and inconsistency in judicial interpretation. Aims: This study aims to analyze legal obstacles and identify appropriate normative frameworks for regulating repeated cassation filings from the perspective of legal certainty. Results: The findings reveal that multiple cassations by debtors contradict the principles of procedural finality, efficiency, and fairness, undermining creditors’ rights and the integrity of commercial court processes. Novelty: The study highlights the urgent need for explicit legislative or Supreme Court guidelines limiting cassation frequency in PKPU to prevent abuse of process. Implications: Strengthening legal certainty in PKPU procedures through regulatory reform will ensure fairness, procedural clarity, and balance between debtor and creditor rights within Indonesia’s commercial justice system. Highlights: Repeated cassation filings undermine the principle of legal finality. Lack of clear regulation in Law No. 37 of 2004 creates legal uncertainty. Reform is needed to limit cassation frequency and ensure procedural fairness. Keywords: PKPU, Cassation, Legal Certainty, Debtor-Creditor, Normative Gap